Adhesion promoting composition and method for producing laminate, as well as film-forming composition and method for producing film
Patent Information
- Application Number
- JP2022521179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-19
- Filing Date
- 2020-11-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-11-16
AI Technical Summary
【0014】 本発明による密着促進組成物によれば、金属層とポリシロキサン層との密着性の高い積層体を形成することができる。また本発明による膜形成組成物によれば、密着性の高い膜を形成することができる。また、形成された積層体または膜は、耐光性に優れている。また、本発明によれば、優れた特性を有するポリシロキサンを含む膜をより簡便に製造することができる。
Smart Images

Figure 0007635220000001 
Figure 0007635220000002 
Figure 0007635220000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesion promoting composition and a method for producing a laminate, as well as a film-forming composition and a method for producing a film. [Background technology]
[0002] Mainly in the field of semiconductors, a siliceous film is formed by applying and curing a liquid composition containing a silicon-containing polymer such as polysiloxane, and is used as an insulating film. Aluminum and copper have traditionally been used as materials for forming wiring on substrates such as semiconductor wafers, but gold and silver are also used. These metals have low reactivity, and when forming the insulating film described above, improving adhesion becomes an issue. Insulating film forming materials for improving adhesion have been proposed (for example, Patent Document 1).
[0003] Gold is used for the wiring of LED elements, which have been attracting particular attention in recent years. Gold has low reactivity, and there is a demand for an insulating film with good adhesion to be easily formed on the wiring. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-52065 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides an adhesion promoting composition capable of forming a laminate having high adhesion between a metal layer and a polysiloxane layer. The present invention also provides a film-forming composition having excellent adhesion. Furthermore, the formed laminate and film have excellent light resistance. [Means for solving the problem]
[0006] The adhesion promoting composition according to the present invention comprises 1. An adhesion promoting composition for use between a metal layer and a polysiloxane layer, comprising: A sulfide compound represented by formula (a): [ka] (In the formula, na is an integer from 1 to 5; X is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted by mercapto, or -L a -Si-R a 3, L a each independently represents an alkylene having 1 to 4 carbon atoms, R a are each independently selected from the group consisting of hydroxy, alkyl having 1 to 4 carbon atoms, and alkoxy having 1 to 4 carbon atoms, wherein the alkyl and alkoxy may be substituted by mercapto, with the proviso that R a at least one of is alkoxy, and solvent The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0007] The method for producing a laminate comprising a metal layer and a polysiloxane layer according to the present invention comprises the steps of: applying the adhesion promoting composition to a metal layer or a polysiloxane layer to form a sulfide compound layer; and Forming a metal layer or a polysiloxane layer on the sulfide compound layer The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0008] The laminate according to the present invention is produced by the method described above.
[0009] An electronic device according to the present invention comprises the above-mentioned laminate.
[0010] The film-forming composition according to the present invention comprises A sulfide compound represented by formula (a): [ka] (In the formula, na is an integer from 1 to 5; X is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted by mercapto, or -L a -Si-R a 3, L a each independently represents an alkylene having 1 to 4 carbon atoms, R a are each independently selected from the group consisting of hydroxy, alkyl having 1 to 4 carbon atoms, and alkoxy having 1 to 4 carbon atoms, wherein the alkyl and alkoxy may be substituted by mercapto, with the proviso that R a at least one of which is alkoxy Polysiloxane, and solvent The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0011] The method for producing a membrane according to the present invention comprises the steps of: applying the film-forming composition to a substrate to form a film-forming composition layer; and Heating the film-forming composition layer The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0012] The membrane according to the present invention is produced by the above-mentioned method.
[0013] An electronic device according to the present invention comprises a film produced by the above method. Effect of the Invention
[0014] According to the adhesion promoting composition of the present invention, a laminate having high adhesion between a metal layer and a polysiloxane layer can be formed. According to the film forming composition of the present invention, a film having high adhesion can be formed. Furthermore, the laminate or film formed has excellent light resistance. According to the present invention, a film containing a polysiloxane having excellent properties can be produced more simply. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, unless otherwise specified, the symbols, units, abbreviations and terms have the following meanings. In this specification, unless otherwise specified, the singular includes the plural, and "a" or "the" means "at least one." In this specification, unless otherwise specified, a concept may be expressed by a plurality of kinds, and when an amount (e.g., mass % or mole %) is described, the amount means the sum of the plurality of kinds. "And / or" includes all combinations of elements and also includes the use of a single element.
[0016] In this specification, when a numerical range is indicated using ~ or -, it includes both endpoints and the units are the same. For example, 5 to 25 mol % means 5 mol % or more and 25 mol % or less.
[0017] In this specification, the term "hydrocarbon" refers to a group containing carbon and hydrogen and, where necessary, oxygen or nitrogen. The term "hydrocarbon group" refers to a monovalent or divalent or higher hydrocarbon group. In this specification, the term "aliphatic hydrocarbon" refers to a linear, branched or cyclic aliphatic hydrocarbon, and the term "aliphatic hydrocarbon group" refers to a monovalent or divalent or higher aliphatic hydrocarbon. The term "aromatic hydrocarbon" refers to a hydrocarbon containing an aromatic ring, which may have an aliphatic hydrocarbon group as a substituent or may be condensed with an alicyclic ring, if necessary. The term "aromatic hydrocarbon group" refers to a monovalent or divalent or higher aromatic hydrocarbon. The term "aromatic ring" refers to a hydrocarbon having a conjugated unsaturated ring structure, and the term "alicyclic ring" refers to a hydrocarbon having a ring structure but not including a conjugated unsaturated ring structure.
[0018] In this specification, alkyl means a group in which one arbitrary hydrogen has been removed from a linear or branched saturated hydrocarbon, and includes linear alkyl and branched alkyl, and cycloalkyl means a group in which one hydrogen has been removed from a saturated hydrocarbon containing a cyclic structure, and optionally includes a linear or branched alkyl in the cyclic structure as a side chain.
[0019] In this specification, aryl refers to a group obtained by removing one arbitrary hydrogen from an aromatic hydrocarbon. Alkylene refers to a group obtained by removing two arbitrary hydrogens from a linear or branched saturated hydrocarbon. Arylene refers to a hydrocarbon group obtained by removing two arbitrary hydrogens from an aromatic hydrocarbon. In this specification, sulfide refers to a divalent group represented by -S-. Polysulfide refers to a group in which multiple -S- are bonded consecutively. For the sake of convenience, -S- contained in thiol (-SH) is also included in sulfide.
[0020] In this specification, "C x~y ", "C x ~C y " and "C x " refers to the number of carbons in a molecule or substituent. For example, C 1~6 Alkyl refers to an alkyl having 1 to 6 carbon atoms (methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.). In addition, as used herein, fluoroalkyl refers to an alkyl group in which one or more hydrogen atoms have been replaced with fluorine, and fluoroaryl refers to an aryl group in which one or more hydrogen atoms have been replaced with fluorine.
[0021] In the present specification, when a polymer has multiple types of repeating units, these repeating units are copolymerized. The copolymerization may be alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, or a mixture thereof. In this specification, % means % by mass, and ratio means mass ratio.
[0022] In this specification, the unit of temperature is Celsius. For example, 20 degrees means 20 degrees Celsius.
[0023] <Adhesion promoting composition> The adhesion promoting composition according to the present invention is used between a metal layer and a polysiloxane layer, and comprises a sulfide compound and a solvent. Here, the adhesion promoting composition according to the present invention is applied to a metal layer before a polysiloxane layer is formed or to a polysiloxane layer before a metal layer is formed, preferably to a metal layer (more preferably to a substrate having a metal surface), and more preferably to metal wiring of a semiconductor element, etc. Metals used for metal wiring include aluminum, copper, silver, gold, molybdenum, chromium, titanium, tungsten, etc., and preferably gold. The materials used in the present invention will now be described.
[0024] [Sulfide compounds] The sulfide compound used in the present invention is represented by the formula (a). [ka] During the ceremony, na is an integer from 1 to 5; X is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted by mercapto, or -L a -Si-R a 3, L a each independently represents an alkylene having 1 to 4 carbon atoms, R a are each independently selected from the group consisting of hydroxy, alkyl having 1 to 4 carbon atoms, and alkoxy having 1 to 4 carbon atoms, wherein the alkyl and alkoxy may be substituted by mercapto, with the proviso that R a At least one of is alkoxy.
[0025] Preferably, the sulfide compound is represented by formula (b) or (c). [ka] During the ceremony, nb is an integer of 1 to 5, preferably an integer of 2 to 5; L b1 and L b2 each independently represents an alkylene having 1 to 4 carbon atoms, R b1 and R b3 each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, preferably methyl or ethyl; R b2 and R b4 are each independently an alkyl group having 1 to 4 carbon atoms, preferably methyl or ethyl; and bp and br each independently represent an integer of 1 to 3, and bq and bs each independently represent an integer of 0 to 2, provided that bp+bq=3 and br+bs=3 are satisfied. It is also a preferred embodiment that bq and bs are 0. [ka] During the ceremony, L c each independently represents an alkylene having 1 to 4 carbon atoms, R c1 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, preferably methyl or ethyl; R c2 is alkyl having 1 to 4 carbon atoms, preferably methyl or ethyl, and Each of cp and cq is independently an integer of 1 to 3, and cr is an integer of 0 to 2, provided that cp+cq+cr=4 is satisfied. In one preferred embodiment, cr is 0.
[0026] Examples of the sulfide compound represented by formula (b) include 3,3-tetrathiobis(propyl)triethoxysilane, 3,3-tetrathiobis(propyl)trimethoxysilane, bis[3-(triethoxysilyl)propyl]pertrisulfide, and bistriethoxysilylpropyl disulfide. Examples of the sulfide compound represented by formula (c) include (3-mercaptopropyl)trimethoxysilane, mercaptomethyltripropoxysilane, mercaptomethyltriethoxysilane, mercaptomethyltrimethoxysilane, (1-mercaptoethyl)triethoxysilane, (2-mercaptoethyl)triethoxysilane, (1-mercaptopropyl)methyldimethoxysilane, (2-mercaptopropyl)methyldimethoxysilane, and (3-mercaptopropyl)methyldimethoxysilane. Examples of suitable silanes include (1-mercaptopropyl)ethyldiethoxysilane, (2-mercaptopropyl)ethyldiethoxysilane, (3-mercaptopropyl)ethyldiethoxysilane, (1-mercaptopropyl)trimethoxysilane, (2-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)trimethoxysilane, (1-mercaptopropyl)triethoxysilane, (2-mercaptopropyl)triethoxysilane, and (3-mercaptopropyl)triethoxysilane.
[0027] The molecular weight of the sulfide compound is preferably 150-800, and more preferably 250-600.
[0028] The sulfide compound used in the present invention contains a structure containing sulfide and a structure containing silicon and alkoxy. Without being bound by theory, -OH is generated by hydrolysis from the alkoxy bonded to silicon, and this -OH and a group (e.g., silanol) present in the polysiloxane layer undergo condensation polymerization to form a bond. In addition, sulfur in the sulfide compound forms a bond with the metal in the metal layer. It is believed that the adhesion promoting effect is achieved by the above two types of bonds.
[0029] The content of the sulfide compound is preferably 0.01 to 5.0 mass %, and more preferably 0.1 to 3.0 mass %, based on the total mass of the composition.
[0030] [solvent] The solvent is not particularly limited as long as it can uniformly dissolve or disperse the sulfide compound and the additives added as necessary and does not affect the metal. Examples of the solvent that can be used in the present invention include: ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether; diethylene glycol monoalkyl ethers such as diethylene glycol monohexyl ether; diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; ethylene glycol alkyl ether acetates such as methyl cellosolve acetate and ethyl cellosolve acetate; Propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether (PGME) and propylene glycol monoethyl ether; Propylene glycol alkyl ether acetates such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, and propylene glycol diacetate; Aromatic hydrocarbons such as benzene, toluene, and xylene, Ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone, Alcohols such as ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, and glycerin, Esters such as ethyl lactate, ethyl 3-ethoxypropionate, and methyl 3-methoxypropionate; Examples include cyclic esters such as γ-butyrolactone. Preferred are diethylene glycol monoalkyl ethers, propylene glycol alkyl ether acetates, propylene glycol monoalkyl ethers, cyclic esters, and esters. More preferably, the solvent comprises at least one selected from the group consisting of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, γ-butyrolactone, propylene glycol diacetate, diethylene glycol monohexyl ether, and methyl 3-methoxypropionate. The solvents are used alone or in combination of two or more, and the amount used varies depending on the coating method and the required film thickness after coating.
[0031] The content of the solvent can be appropriately selected taking into consideration the coating method to be adopted. The content of the solvent is preferably 1 to 90 mass %, more preferably 20 to 70 mass %, based on the total mass of the composition.
[0032] The composition according to the present invention essentially contains a sulfide compound and a solvent, but may contain an additional compound in combination, if necessary.
[0033] [Surfactants] The surfactant can be added for the purpose of improving coating properties, developability, etc. Examples of the surfactant that can be used in the present invention include nonionic surfactants, anionic surfactants, and amphoteric surfactants.
[0034] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, and polyoxyethylene cetyl ether; acetylene glycol derivatives such as polyoxyethylene fatty acid diesters, polyoxyethylene fatty acid monoesters, polyoxyethylene polyoxypropylene block polymers, acetylene alcohol, acetylene glycol, polyethoxylates of acetylene alcohol, and polyethoxylates of acetylene glycol; fluorine-containing surfactants such as Fluorad (trade name, Sumitomo 3M Limited), Megafac (trade name, DIC Corporation), and Sulfuron (trade name, Asahi Glass Co., Ltd.); and organic siloxane surfactants such as KP341 (trade name, Shin-Etsu Chemical Co., Ltd.). Examples of the acetylene glycol include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,5-dimethyl-1-hexyne-3-ol, 2,5-dimethyl-3-hexyne-2,5-diol, and 2,5-dimethyl-2,5-hexanediol.
[0035] Examples of the anionic surfactant include ammonium salts or organic amine salts of alkyldiphenyl ether disulfonic acids, ammonium salts or organic amine salts of alkyldiphenyl ether sulfonic acids, ammonium salts or organic amine salts of alkylbenzene sulfonic acids, ammonium salts or organic amine salts of polyoxyethylene alkyl ether sulfates, and ammonium salts or organic amine salts of alkyl sulfates.
[0036] Further, examples of amphoteric surfactants include 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazolium betaine, lauric acid amidopropyl hydroxysulfone betaine, and the like.
[0037] These surfactants can be used alone or in combination of two or more kinds, and the content thereof is preferably from 0.005 to 1 mass %, more preferably from 0.01 to 0.5 mass %, based on the total mass of the composition.
[0038] [Other additives] The adhesion promoting composition according to the present invention may be combined with other compounds other than those described above as other additives. The content of the other additives is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the composition.
[0039] <Method of manufacturing a laminate using an adhesion promoting composition> The method for producing a laminate comprising a metal layer and a polysiloxane layer according to the present invention comprises the steps of: applying the adhesion promoting composition according to the present invention to a metal layer or a polysiloxane layer to form a sulfide compound layer; and The method comprises forming a metal layer or a polysiloxane layer on a sulfide compound layer. A sulfide compound layer may be formed on a metal layer, and then a polysiloxane layer may be formed thereon, or a sulfide compound layer may be formed on a polysiloxane layer, and then a metal layer may be formed thereon.
[0040] A preferred method for producing a laminate comprising a metal layer and a polysiloxane layer includes the steps of: applying the adhesion promoting composition of the present invention to a metal layer to form a sulfide compound layer; applying a composition containing polysiloxane to the sulfide compound layer to form a polysiloxane layer; The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0041] The metal layer is preferably a substrate having a metal surface. The substrate used for the substrate having a metal surface may be a suitable substrate such as a silicon substrate, a glass substrate, or a resin film. The metal may be gold, silver, copper, aluminum, molybdenum, chromium, titanium, or tungsten, and gold is preferred. The substrate having a metal surface is preferably a substrate having metal wiring.
[0042] The adhesion promoting composition can be applied by any method conventionally known as a composition application method, specifically, any method can be selected from dip coating, roll coating, bar coating, brush coating, spray coating, doctor coating, flow coating, spin coating, slit coating, etc.
[0043] After the adhesion promoting composition is applied, the coating film may be prebaked (heat-treated) as necessary to dry the coating film and reduce the amount of remaining solvent. The prebaking step is generally performed at a temperature of 70 to 150°C, preferably 90 to 140°C, for 10 to 180 seconds, preferably 30 to 90 seconds, when using a hot plate, and for 1 to 30 minutes when using a clean oven. It is also a preferred embodiment not to perform prebaking.
[0044] A composition containing a polysiloxane is applied onto the formed sulfide compound layer. The composition containing a polysiloxane preferably contains, for example, a polysiloxane described below, a thermal acid generator or a thermal base generator described below, the above surfactant, and the above solvent.
[0045] The method of applying the composition containing polysiloxane is the same as above, and after application, the coating film is prebaked (heat-treated) as necessary to dry the coating film and reduce the amount of remaining solvent. This prebaking step can be carried out at a temperature of generally 70 to 150° C., preferably 90 to 140° C., for 10 to 180 seconds, preferably 30 to 90 seconds, when using a hot plate, or for 1 to 30 minutes when using a clean oven.
[0046] After the above pre-baking is performed as necessary, further heating can be performed. This heating can cure the coating film. The heating temperature in this heating step is not particularly limited as long as it is a temperature at which the dehydration condensation of polysiloxane can proceed and the coating film can be cured, and can be determined arbitrarily. However, if silanol groups remain, the chemical resistance of the cured film may become insufficient, or the leakage current of the cured film may increase. From this viewpoint, the heating temperature is generally selected to be relatively high. In order to promote the curing reaction and obtain a sufficient cured film, the heating temperature is preferably 130 to 300°C, more preferably 180 to 250°C. In addition, the heating time is not particularly limited, and is generally 1 minute to 2 hours, preferably 5 minutes to 30 minutes. The heating time is the time after the temperature of the film reaches the desired heating temperature. Usually, it takes several minutes to several hours for the film to reach the desired temperature from the temperature before heating. Heating is performed in an oxygen-containing atmosphere such as an inert gas atmosphere or air.
[0047] <Electronic elements> The laminate according to the present invention may be subjected to post-treatments such as processing and circuit formation, as required, to form an electronic device. Any conventionally known method may be used for these post-treatments.
[0048] <Film forming composition> The film-forming composition according to the present invention comprises a sulfide compound, a polysiloxane, and a solvent. The sulfide compound and the solvent are as described above.
[0049] [Polysiloxane] The polysiloxane used in the present invention is not particularly limited and can be selected from any one according to the purpose. The skeleton structure of polysiloxane can be classified into silicone skeleton (the number of oxygen atoms bonded to silicon atom is 2), silsesquioxane skeleton (the number of oxygen atoms bonded to silicon atom is 3), and silica skeleton (the number of oxygen atoms bonded to silicon atom is 4) according to the number of oxygen atoms bonded to silicon atom. In the present invention, any of these may be used. The polysiloxane molecule may contain a combination of multiple of these skeleton structures.
[0050] Preferably, the polysiloxane used in the present invention comprises repeat units represented by formula (Ia). [ka] During the ceremony, R Ia is hydrogen, C 1~30 (Preferably C 1~10 ) represents a linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbon group; The aliphatic hydrocarbon group and the aromatic hydrocarbon group are each unsubstituted or substituted with fluorine, hydroxy or alkoxy; and In the aliphatic hydrocarbon group and the aromatic hydrocarbon group, methylene is not replaced or one or more methylenes are replaced by oxy, imino or carbonyl, provided that R Ia is not hydroxy or alkoxy. The above methylene includes the terminal methyl. In addition, the above-mentioned "substituted with fluorine, hydroxy or alkoxy" means that a hydrogen atom directly bonded to a carbon atom in the aliphatic hydrocarbon group and aromatic hydrocarbon group is replaced with fluorine, hydroxy or alkoxy. The same applies to other similar descriptions in this specification.
[0051] In the repeating unit represented by formula (Ia), R IaExamples of R include (i) alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, and decyl, (ii) aryl groups such as phenyl, tolyl, and benzyl, (iii) fluoroalkyl groups such as trifluoromethyl, 2,2,2-trifluoroethyl, and 3,3,3-trifluoropropyl, (iv) fluoroaryl groups, (v) cycloalkyl groups such as cyclohexyl, (vi) nitrogen-containing groups having an amino or imide structure such as isocyanate and amino, and (vii) oxygen-containing groups having an epoxy structure such as glycidyl, or an acryloyl structure or methacryloyl structure. Preferred are methyl, ethyl, propyl, butyl, pentyl, hexyl, and phenyl. R Ia When R is methyl, the raw material is easily available, the hardness of the film after curing is high, and the film has high chemical resistance, which is preferable. Ia When the group is phenyl, this is preferable because it increases the solubility of the polysiloxane in a solvent and makes the cured film less likely to crack.
[0052] The polysiloxane used in the present invention may further contain a repeating unit represented by formula (Ib). [ka] During the ceremony, R Ib is a group formed by removing multiple hydrogens from a nitrogen- and / or oxygen-containing cyclic aliphatic hydrocarbon compound, including amino, imino, and / or carbonyl.
[0053] In formula (Ib), R Ib R is preferably a group in which multiple hydrogen atoms, preferably two or three hydrogen atoms, have been removed from a nitrogen-containing aliphatic hydrocarbon ring containing imino and / or carbonyl, more preferably a five- or six-membered ring containing nitrogen as a constituent member. Examples of R include groups in which two or three hydrogen atoms have been removed from piperidine, pyrrolidine, and isocyanurate. Ib connects Si groups contained in multiple repeating units together.
[0054] The polysiloxane used in the present invention may further contain a repeating unit represented by formula (Ic). [ka]
[0055] If the compounding ratio of the repeating units represented by formula (Ib) and formula (Ic) is high, the compatibility with solvents and additives may decrease and the film stress may increase, which may make cracks more likely to occur. Therefore, the compounding ratio of the repeating units represented by formula (Ib) and formula (Ic) is preferably 40 mol % or less, and more preferably 20 mol % or less, based on the total number of repeating units of the polysiloxane.
[0056] The polysiloxane used in the present invention may further contain a repeating unit represented by the following formula (Id): [ka] During the ceremony, R Id are each independently hydrogen, C 1~30 (Preferably C 1~10 ) represents a linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbon group; The aliphatic hydrocarbon group and the aromatic hydrocarbon group are each unsubstituted or substituted with fluorine, hydroxy or alkoxy; and In the aliphatic hydrocarbon group and the aromatic hydrocarbon group, methylene is not replaced or is replaced by oxy, imido or carbonyl.
[0057] In the repeating unit represented by formula (Id), R IdExamples of R include (i) alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, and decyl, (ii) aryl groups such as phenyl, tolyl, and benzyl, (iii) fluoroalkyl groups such as trifluoromethyl, 2,2,2-trifluoroethyl, and 3,3,3-trifluoropropyl, (iv) fluoroaryl groups, (v) cycloalkyl groups such as cyclohexyl, (vi) nitrogen-containing groups having an amino or imide structure such as isocyanate and amino, and (vii) oxygen-containing groups having an epoxy structure such as glycidyl, or an acryloyl structure or methacryloyl structure. Methyl, ethyl, propyl, butyl, pentyl, hexyl, and phenyl are preferred. R Id When R is methyl, the raw material is easily available, the hardness of the film after curing is high, and the film has high chemical resistance, which is preferable. Id When the group is phenyl, this is preferable because it increases the solubility of the polysiloxane in a solvent and makes the cured film less likely to crack.
[0058] By having the repeating unit of the above formula (Id), the polysiloxane of the present invention can have a partially linear structure. However, since heat resistance decreases, it is preferable that the linear structure portion is small. Specifically, the repeating unit of the formula (Id) is preferably 30 mol % or less, more preferably 5 mol % or less, based on the total number of repeating units of the polysiloxane. It is also an embodiment of the present invention that the repeating unit of the formula (Id) is not present (0 mol %).
[0059] The polysiloxane used in the present invention may contain two or more kinds of repeating units. For example, R Ia is methyl, a repeating unit represented by formula (Ia) in which R is 1, a repeating unit represented by formula (Ic) in which R is 1, and a repeating unit represented by formula (Ic).
[0060] The polysiloxane used in the present invention preferably has silanol. Here, silanol refers to a compound in which an OH group is directly bonded to the Si skeleton of the polysiloxane, and in the polysiloxane containing the repeating units of the above formulas (Ia) to (Id), a hydroxyl group is directly bonded to the silicon atom. That is, the -O group in the above formulas (Ia) to (Id) 0.5 -O 0.5 Silanol is formed by bonding with H. The content of silanol in polysiloxane varies depending on the synthesis conditions of polysiloxane, such as the monomer mixing ratio and the type of reaction catalyst. The content of this silanol can be evaluated by quantitative infrared absorption spectroscopy measurement. The absorption band assigned to silanol (SiOH) is 900±100 cm in the infrared absorption spectrum. -1 The intensity of this absorption band increases when the silanol content is high.
[0061] In the present invention, in order to quantitatively evaluate the silanol content, the intensity of the absorption band attributed to Si-O is used as the standard. -1 An absorption band having a peak in the range of is adopted. The silanol content can be relatively evaluated based on the ratio S2 / S1 of the integrated intensity S2 of the absorption band attributed to SiOH to the integrated intensity S1 of the absorption band attributed to Si-O. In the present invention, the ratio S2 / S1 is preferably 0.003 to 0.15, and more preferably 0.01 to 0.10.
[0062] The intensity of the absorption band is determined taking into consideration noise in the infrared absorption spectrum. A typical infrared absorption spectrum of polysiloxane has a band intensity of 900±100 cm -1 The absorption band attributable to Si-OH has a peak in the range of 1100±100cm -1The absorption bands attributable to Si-O, which have peaks in the range of 1000 to 15000 nm, are confirmed. The area intensity of these absorption bands can be measured as an area taking into consideration a baseline that takes noise and the like into account. It is possible that the tail of the absorption band attributable to Si-OH and the tail of the absorption band attributable to Si-O overlap, and in that case, the wave number corresponding to the minimum point between the two absorption bands in the spectrum is used as the boundary. The same applies when the tail of other absorption bands overlaps with the tail of the absorption band attributable to Si-OH or Si-O.
[0063] The mass average molecular weight of the polysiloxane used in the present invention is not particularly limited. However, the higher the molecular weight, the more the coating property tends to be improved. On the other hand, the lower the molecular weight, the fewer the restrictions on synthesis conditions, and the easier the synthesis, while polysiloxanes with very high molecular weights are difficult to synthesize. For these reasons, the mass average molecular weight of the polysiloxane is usually 500 to 25,000, and from the viewpoint of solubility in organic solvents, it is preferably 1,000 to 20,000. Here, the mass average molecular weight is the polystyrene-equivalent mass average molecular weight, and can be measured by gel permeation chromatography using polystyrene as a standard.
[0064] [Method of synthesizing polysiloxane] The method for synthesizing the polysiloxane used in the present invention is not particularly limited, but for example, R ia -Si-(OR ia’ )3(ia) (In the formula, R ia is hydrogen, C 1~30 (Preferably C 1~10 ) represents a linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbon group; the aliphatic hydrocarbon group and the aromatic hydrocarbon group are each unsubstituted or substituted with fluorine, hydroxy or alkoxy; In the aliphatic hydrocarbon group and the aromatic hydrocarbon group, methylene is not replaced or is replaced by oxy, imido or carbonyl; and R ia’ is linear or branched, C 1~6 (It is alkyl) A silane monomer represented by the formula: can be obtained by hydrolyzing and polymerizing the compound in the presence of an acidic or basic catalyst, as necessary.
[0065] In the formula (ia), preferred R ia’ Examples of R include methyl, ethyl, n-propyl, isopropyl, and n-butyl. ia’ There are multiple R ia’ may be the same or different. Preferred R ia is the above R Ia These are the same as those listed as preferred in the above.
[0066] Specific examples of the silane monomer represented by formula (ia) include methyltrimethoxysilane, methyltriethoxysilane, methyltriisopropoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltriisopropoxysilane, ethyltri-n-butoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-butyltrimethoxysilane, n-butyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, decyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, trifluoromethyltrimethoxysilane, trifluoromethyltriethoxysilane, and 3,3,3-trifluoropropyltrimethoxysilane. Among them, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, and phenyltrimethoxysilane are preferred. It is preferred to combine two or more types of silane monomer represented by formula (ia).
[0067] Furthermore, a silane monomer represented by the following formula (ic) may be combined: When the silane monomer represented by formula (ic) is used, a polysiloxane containing the repeating unit (Ic) can be obtained. Si(OR ic’ )4(ic) In the formula, R ic’ is linear or branched, C 1~6 Alkyl In formula (ic), preferred R ic’ Examples of R include methyl, ethyl, n-propyl, isopropyl, and n-butyl. ic’ There are multiple R ic’ may be the same or different. Specific examples of the silane monomer represented by formula (ic) include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, and the like.
[0068] A silane monomer represented by the following formula (ib) can also be further combined. R ib -Si-(OR ib’ )3(ib) During the ceremony, R ib’ is linear or branched, C 1~6 R is an alkyl group, for example, methyl, ethyl, n-propyl, isopropyl, and n-butyl. ib’ is contained multiple times in one monomer, but each R ib’ may be the same or different, R ib is a group obtained by removing multiple hydrogens, preferably two or three hydrogens, from a nitrogen- and / or oxygen-containing cyclic aliphatic hydrocarbon compound, including amino, imino, and / or carbonyl. ib is the above R Ib These are the same as those listed as preferred in the above.
[0069] Specific examples of the silane monomer represented by formula (ib) include tris-(3-trimethoxysilylpropyl)isocyanurate, tris-(3-triethoxysilylpropyl)isocyanurate, and tris-(3-trimethoxysilylethyl)isocyanurate.
[0070] Furthermore, a silane monomer represented by the following formula (id) may be combined: When the silane monomer represented by formula (id) is used, a polysiloxane containing a repeating unit (Id) can be obtained. (R id )2-Si-(OR id’ )2(id) During the ceremony, R id’ are each independently linear or branched, C 1~6 R is an alkyl group, for example, methyl, ethyl, n-propyl, isopropyl, and n-butyl. id’ is contained multiple times in one monomer, but each R id’ may be the same or different, R id are each independently hydrogen, C 1~30 (Preferably C 1~10 ) represents a linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic hydrocarbon group; The aliphatic hydrocarbon group and the aromatic hydrocarbon group are each unsubstituted or substituted with fluorine, hydroxy or alkoxy; and In the aliphatic hydrocarbon group and the aromatic hydrocarbon group, methylene is not replaced or is replaced by oxy, imido or carbonyl. id is the above R Id are listed as preferred in the above.
[0071] [Thermal acid generator or thermal base generator] The film-forming composition according to the present invention preferably further comprises a thermal acid generator or a thermal base generator, which is preferably selected depending on the polymerization or crosslinking reaction to be utilized in the film production process.
[0072] The optimum content of these varies depending on the type and amount of active substance generated by decomposition. If the content is too high, cracks may occur in the film formed, or coloring due to the decomposition may become significant, resulting in a decrease in the colorless transparency of the film. In addition, thermal decomposition may cause deterioration of the electrical insulation of the cured product or gas emission, which may cause problems in subsequent processes. Therefore, the content of the thermal acid generator or thermal base generator is preferably 0.1 to 10 mass %, more preferably 0.5 to 5 mass %, based on the total mass of the polysiloxane.
[0073] In the present invention, the thermal acid generator or thermal base generator refers to a compound that generates an acid or a base by bond cleavage caused by heat. It is preferable that these do not generate an acid or a base or generate only a small amount of an acid or a base by the heat during pre-baking after coating of the composition. Examples of thermal acid generators include salts and esters that generate organic acids, such as various aliphatic sulfonic acids and their salts, various aliphatic carboxylic acids and their salts, such as citric acid, acetic acid, and maleic acid, various aromatic carboxylic acids and their salts, such as benzoic acid and phthalic acid, aromatic sulfonic acids and their ammonium salts, various amine salts, aromatic diazonium salts, and phosphonic acids and their salts. Among the thermal acid generators, salts of organic acids and organic bases are particularly preferred, and salts of sulfonic acids and organic bases are more preferred. Preferred sulfonic acids include p-toluenesulfonic acid, benzenesulfonic acid, p-dodecylbenzenesulfonic acid, 1,4-naphthalenedisulfonic acid, and methanesulfonic acid. These thermal acid generators can be used alone or in combination.
[0074] Examples of thermal base generators include compounds that generate bases such as imidazole and tertiary amines, and mixtures thereof. Examples of bases that are released include imidazole derivatives such as N-(2-nitrobenzyloxycarbonyl)imidazole, N-(3-nitrobenzyloxycarbonyl)imidazole, N-(4-nitrobenzyloxycarbonyl)imidazole, N-(5-methyl-2-nitrobenzyloxycarbonyl)imidazole, and N-(4-chloro-2-nitrobenzyloxycarbonyl)imidazole, and 1,8-diazabicyclo[5.4.0]undecene-7. These base generators can be used alone or in combination, as with acid generators.
[0075] [Other additives] The film-forming composition according to the present invention may contain, as other additives, the above-mentioned surfactants, etc. The content of the other additives is preferably 5% by mass or less, more preferably 1% by mass or less, based on the total mass of the composition.
[0076] <Method for forming a film using the film-forming composition> The method for forming a film according to the present invention comprises the steps of: applying a film-forming composition to a substrate to form a film-forming composition layer; and Heating the film-forming composition layer The present invention relates to a method for producing a semiconductor device comprising the steps of:
[0077] The substrate is not particularly limited, and suitable substrates such as silicon substrates, glass substrates, and resin films can be used. The substrate is preferably a substrate having a metal surface, and more preferably a substrate having metal wiring. The metal of the metal wiring can be gold, silver, copper, aluminum, molybdenum, chromium, titanium, tungsten, etc., and gold is preferred. It is also a preferred embodiment of the present invention to form a film on a substrate not having a metal surface using the film-forming composition of the present invention, and then form a metal layer thereon.
[0078] The film-forming composition of the present invention can be applied by any method conventionally known as a method for applying a composition, specifically, any method can be selected from dip coating, roll coating, bar coating, brush coating, spray coating, doctor coating, flow coating, spin coating, slit coating, etc.
[0079] After coating the film-forming composition of the present invention, the coating can be prebaked (heat-treated) to dry the coating and reduce the amount of remaining solvent. The prebaking step can be carried out at a temperature of generally 70 to 150° C., preferably 90 to 140° C., for 10 to 180 seconds, preferably 30 to 90 seconds, when using a hot plate, or for 1 to 30 minutes when using a clean oven.
[0080] The formed film-forming composition layer is further heated to harden the coating film and form a film. The heating temperature in this heating step is not particularly limited as long as it is a temperature at which the dehydration condensation of polysiloxane proceeds and the coating film can be hardened, and can be determined arbitrarily. However, if silanol remains, the chemical resistance of the film may become insufficient, or the leakage current of the film may increase. From this viewpoint, the heating temperature is generally selected to be relatively high. In order to promote the curing reaction and obtain a sufficient film, the heating temperature is preferably 130 to 300°C, more preferably 180 to 250°C. In addition, the heating time is not particularly limited, and is generally 1 minute to 2 hours, preferably 5 minutes to 30 minutes. The heating time is the time after the temperature of the pattern film reaches the desired heating temperature. Usually, it takes several minutes to several hours for the pattern film to reach the desired temperature from the temperature before heating. Heating is performed in an oxygen-containing atmosphere such as an inert gas atmosphere or air.
[0081] <Electronic elements> The film according to the present invention has excellent insulating properties and can be used as an insulating film. The formed insulating film is then subjected to post-treatment such as processing and circuit formation as necessary to form an electronic device. Any conventionally known method can be used for these post-treatments.
[0082] Working Example The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples and comparative examples. <Example 101> The sulfide compound 3,3'-tetrathiobis(propyltriethoxysilane) was added to the solvent PGMEA so as to have a concentration of 2 mass % and the surfactant KF-53 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added to have a concentration of 0.5 mass %, and the mixture was stirred to prepare the adhesion promoting composition of Example 101.
[0083] <Examples 102 to 106, Comparative Examples 101 and 102> Adhesion promoting compositions of Examples 102 to 106 and Comparative Examples 101 and 102 were prepared in the same manner as in Example 101, except that the type and concentration of the sulfide compound and the solvent were changed as shown in Table 1. [Table 1]
[0084] <Example 201> In a 2L flask equipped with a stirrer, a thermometer, and a cooling tube, 49.0 g of 25% by mass tetramethylammonium hydroxide aqueous solution, 600 ml of isopropyl alcohol (IPA), and 4.0 g of water were charged, and then a mixed solution of 60 g of methyltrimethoxysilane and 40 g of phenyltrimethoxysilane was prepared in a dropping funnel. The mixed solution was dropped at 40°C, stirred at the same temperature for 2 hours, and then neutralized by adding a 10% by mass HCl aqueous solution. 400 ml of toluene and 600 ml of water were added to the neutralized liquid, which was separated into two phases and the aqueous phase was removed. The mixture was further washed three times with 300 ml of water, and the obtained organic phase was concentrated under reduced pressure to remove the solvent, and PGMEA was added to the concentrate so that the solid concentration was 35% by mass, to obtain a polysiloxane A solution. The molecular weight (polystyrene equivalent) of the obtained polysiloxane A was measured by gel permeation chromatography, and it was found that the mass average molecular weight was 1,400.
[0085] To the polysiloxane A solution obtained above, 1 mass % of the sulfide compound 3,3'-tetrathiobis(propyltriethoxysilane), 0.5 mass % of a thermal base generator (1,8-diazabicyclo(5.4.0)undecene-7-orthophthalic acid salt), and 0.5 mass % of a surfactant KF-53 (manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and PGMEA was further added so that the solid concentration was 35 mass %, and the mixture was stirred to prepare the siliceous film-forming composition of Example 201.
[0086] <Examples 202 to 204, Comparative Examples 201 and 202> Film-forming compositions of Examples 202 to 204 and Comparative Examples 201 and 202 were prepared in the same manner as in Example 201, except that the type and concentration of the sulfide compound and the solvent were changed as shown in Table 2. [Table 2]
[0087] <Formation of Laminate> The adhesion promoting composition of Examples 101 to 106, Comparative Example 101, or 102 was applied by spin coating to a substrate of gold attached to a silicon wafer so as to have an average film thickness of 50 nm. Polysiloxane composition A was applied thereon by spin coating to have an average film thickness of 2 μm, and heated on a hot plate at 130° C. for 90 seconds to form a laminate of Examples 101 to 106, Comparative Example 101, or 102.
[0088] <Membrane formation> The film-forming compositions of Examples 201 to 204 and Comparative Examples 201 and 202 were applied by spin coating to a substrate consisting of a silicon wafer coated with gold to an average film thickness of 2 μm, and the composition was heated on a hot plate at 130° C. for 90 seconds to form the films of Examples 201 to 204 and Comparative Examples 201 and 202.
[0089] <Adhesion evaluation> The obtained laminate or film was cut to a width of 1 mm and a hatch number of 25 in accordance with JIS K5600. A peeling tape (Nichiban CT24 (adhesive strength 4.01 N / 10 mm)) was attached and then peeled off, and the cut surface was observed and evaluated as follows. The obtained results are shown in Tables 1 and 2. A: No peeling was observed on the film. B: Peeling of the film was not observed visually, but peeling was confirmed at the edge using a microscope. C: Peeling of the film was visually confirmed over the entire surface. When a film was formed in the same manner as in Example 202 using the above polysiloxane composition A, the result of the adhesion evaluation was C.
[0090] <Light resistance evaluation> The obtained polysiloxane layer or film was measured using a spectrophotometer CM-5 (Konica Minolta) * , b * and L * The values were then measured in a Q-SUN xenon arc tester (Q-Lab Corporation) at a temperature of 25°C, a Xe-Arc light source, and an illuminance of 75 W / m 2 The film was then left at 20 million Lux for 24 hours. * , b * and L * The change in each (Δa * , Δb * , and ΔL * The uncoated substrates in Tables 1 and 2 are silicon substrates with gold attached, and for comparison, similar light resistance evaluations were also carried out using these substrates. The measurement result is Δa * was as shown in Tables 1 and 2. * and ΔL * was approximately the same in both the Examples and the Comparative Examples.
Claims
1. 1. An adhesion promoting composition for use between a metal layer and a polysiloxane layer, comprising: A sulfide compound represented by formula (a): 【Chemistry 1】 (In the formula, n a is an integer from 1 to 5, X is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms which may be substituted by mercapto, or -L a -Si-R a 3 and L a are each independently an alkylene having 1 to 4 carbon atoms, R a are each independently selected from the group consisting of hydroxy, alkyl having 1 to 4 carbon atoms, and alkoxy having 1 to 4 carbon atoms, wherein the alkyl and alkoxy are optionally substituted by mercapto, with the proviso that R a at least one of is alkoxy; and solvent comprising The adhesion promoting composition, wherein the solvent comprises at least one selected from the group consisting of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, γ-butyrolactone, propylene glycol diacetate, diethylene glycol monohexyl ether, and methyl 3-methoxypropionate.
2. The composition according to claim 1 , wherein the sulfide compound is represented by formula (b) or (c). 【Chemistry 2】 (In the formula, nb is an integer from 1 to 5, L b1 and L b2 are each independently an alkylene having 1 to 4 carbon atoms, R b1 and R b3 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, R b2 and R b4 are each independently an alkyl group having 1 to 4 carbon atoms; and bp and br each independently represent an integer of 1 to 3, and bq and bs each independently represent an integer of 0 to 2, provided that bp+bq=3 and br+bs=3 are satisfied. 【Chemistry 3】 (In the formula, L c are each independently an alkylene having 1 to 4 carbon atoms, R c1 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, R c2 is an alkyl group having 1 to 4 carbon atoms; and cp and cq each independently represent an integer of 1 to 3, and cr represents an integer of 0 to 2, provided that cp+cq+cr=4 is satisfied.
3. The composition according to claim 1 or 2, wherein the molecular weight of the sulfide compound is 150 to 800.
4. The composition according to any one of claims 1 to 3, further comprising a surfactant.
5. A method for producing a laminate comprising a metal layer and a polysiloxane layer, comprising the steps of: Applying the adhesion promoting composition according to any one of claims 1 to 4 to a metal layer or a polysiloxane layer to form a sulfide compound layer; and forming a metal layer or a polysiloxane layer on the sulfide compound layer; The method comprising:
6. Applying the adhesion promoting composition according to any one of claims 1 to 4 to a metal layer to form a sulfide compound layer; and applying a composition containing polysiloxane to the sulfide compound layer to form a polysiloxane layer; The method of claim 5, comprising:
7. A laminate produced by the method according to claim 5 or 6.
8. An electronic device comprising the laminate according to claim 7 .
Citation Information
Patent Citations
Primer composition
JP2002226777A
Sulfur-containing organic-inorganic hybrid insulating film
JP2011052065A